Reconfiguration of organizational knowledge: the case of teleworkers during isolation in Córdoba, Argentina (Journal of Management & Business, 2022)
The epistemic-ontological positioning to which we adhere understands the signifier not as a simple tool for use, but on the contrary, as a constitutive element of subjectivities and organizations. The notion of speaking beings is importantly sustained by the ascription, belonging and articulation to the system of signs that configures the social space from a macro perspective. In this line, we consider work as a device to produce subjectivities, understanding that the notion of subjectivity is structured situationally; that is why each stage of history generates unique modes of production. It is a permanent process that occurs in the interplay between the social and the subjective. The intention of this research has been to make visible the processes of subjectivation present in the new work organizations imposed by the health situation of COVID-19, which we proposed to read across the categories of time and space. We take the category of plusmodern subjectivities to synthesize the processes of subjective articulation against social discourses in general and neo-management in particular, whose elements and computer signifiers are characterized by the erasure of limits, the non-recognition of the lack and primacy of superego enjoyment tending to overload and consume the subject. For this, a qualitative study of discourse analysis was carried out, through semi-structured interviews, using observation dimensions established from the previous research framework and conceptual categories introduced in this article. The selection of participants was carried out by means of an intentional non-probabilistic sampling. The sample consisted of 10 people who were working full time in organizations in Córdoba, Argentina.
Keywords: knowledge; management; work environment; health; pandemics